Economic Evaluation of Tandem Mass Spectrometry Newborn Screening in Australia - Norman, Richard; Haas, M.; Chaplin, M.; Joy, P.; Wilcken, B. (American Academy of Pediatrics, 2009)
OBJECTIVE. The goal was to investigate the cost-effectiveness of tandem mass spectrometry screening for the detection of inborn metabolic errors in an Australian setting.METHODS. Cost-effectiveness analysis from the health service perspective was undertaken on the basis of registry data for affected individuals. The intervention group was contrasted with both a contemporaneous group in nonscreening states and a historical cohort. The registry covers all individuals identified in Australia between 1994 and 2002. Main outcome measures were the total net cost of screening, the cost of treatment, life-years saved, and deaths averted.RESULTS. The total net cost of testing was estimated to be A$218 000 per 100 000 infants. Medical costs incurred by the intervention group exceeded those for the control group by A$131 000 per 100 000 infants. The number of life-years saved per 100 000 infants screened was 32.378 life-years per 100 000 infants through an expected mortality rate reduction of 0.738 deaths per 100 000 infants. The cost per death averted was estimated to be A$472 913 and the cost per life-year saved was estimated to be A$10 779, which compare favorably with existing cost-effectiveness standards. This conclusion is particularly robust because conservative assumptions were made throughout, because of data limitations. Sensitivity analyses suggested that this result was relatively robust to adjustment of model parameters.CONCLUSIONS. Tandem mass spectrometry screening for conditions caused by rare errors of metabolism is likely to be a cost-effective intervention in Australia.